Development and validation of the osteoporosis patient satisfaction questionnaire (OPSQ) - Lai, P.S.; Chua, S.S.; Chan, S.P.; Low, W.Y.; Wong, I.C. (2010)
OBJECTIVES: To develop and validate the Osteoporosis Patient Satisfaction Questionnaire (OPSQ) and to assess the opinion of postmenopausal osteoporotic women towards pharmaceutical care. METHODS: A 16-item instrument was designed. Each response consists of a five-point Likert-like scale with higher scores indicating greater satisfaction. The face and content validity was established via consultation with an endocrinologist and three pharmacists as well as feedback from participants in a preliminary study. Postmenopausal osteoporotic women taking bisphosphonates were recruited and randomly allocated to the intervention (n=90) and control groups (n=90). Pharmaceutical care was provided at month 2 to the intervention group while the control group received standard pharmacy services. The OPSQ was administered at month 6 (end of the intervention period), to assess patients' satisfaction. Factor analysis was performed using varimax rotation. Internal reliability was established using Cronbach's alpha. Construct validity was performed by using the Mann-Whitney U test. RESULTS: The internal reliability of the OPSQ produced a Cronbach's alpha of 0.86. Factor analysis identified one component in the OPSQ, which measured patient satisfaction. The intervention group showed significantly better overall OPSQ score than the control group (91.89+/-7.22 versus 84.32+/-7.48, p<0.001). This indicates that the OPSQ was able to differentiate between participants who received pharmaceutical care from those who did not. CONCLUSIONS: The 16-item OPSQ developed in this study has high internal reliability and is a valid instrument for assessing osteoporotic women's satisfaction with pharmaceutical care service in Malaysia.